Existence and blow up of solutions for a class of parabolic problems with dynamical boundary condition - Anass Lamaizi; Abdellah Zerouali; Omar Chakrone; Belhadj Karim (Statistics, Optimization & Information Computing, 2023)
In this paper, we study weak solutions for a class of parabolic problems with dynamical boundary condition.We establish the existence of a weak solution to the corresponding Dynamical problem. Moreover, we will show that the existence time T of solution is finite when the initial energy satisfies certain condition.